Elaboración del estudio de prefactibilidad para el montaje de una empresa procesadora de alimentos extruidos tipo Snacks horneados,a partir de salvado de trigo. (2018)
This document is focused on a pre-feasibility study for the assembly of an extruded food processing company that will have snacks prepared from wheat bran as snacks. Wheat bran is of great nutritional interest because of its fiber content and currently the wheat milling industry generates large quantities of this by-product. Which is used mainly for animal consumption, so it requires a healthy product with good fiber source different from traditional snacks that are not very nutritious